Effects of perioperative statin treatment on postoperative atrial fibrillation and cardiac mortality in patients undergoing coronary artery bypass grafting: a propensity score analysis - Ayşegül Kunt; Sedat Özcan; Aslihan Küçüker; Dolunay Odabaşi; Alper Sami Kunt (Medicinski glasnik, 2015)
Aim: To evaluate the effect of perioperative statin treatment on postoperative atrial fibrillation and cardiac mortality in patients undergoing coronary artery bypass grafting. Methods: A total of 1890 patients who underwent isolated coronary artery bypass were analyzed retrospectively, of which 425 patients (22.4%) older than 70 were included in the study. The demographic properties, preoperative, operative and postoperative data and other medications of these patients were recorded. Continuous preoperative and postoperative atorvastatin therapy were received by 124 (29.17%) patients; 301 (70.82%) patients were matched to a control group (no-statin group). The two groups were matched by propensity score analysis in terms of atrial fibrillation development and cardiac mortality. Results: Medical history, medical treatment, cardiovascular history, and operative characteristics demonstrated significant heterogeneity in both groups. Postoperative atrial fibrillation was similar in both groups. Before propensity score matching, the percentages of patients in postoperative atrial fibrillation with respect to Atorvastain-group and No-statin-group were 13.71 and 10.3 respectively; however, those were 13.71 and 14.51 after matching. In a multivariate regression analysis, five-vessel bypass (odds ratio OR, 2.354; 95% confidence interval CI, 0.99 to 5.57) was an independent predictor of postoperative atrial fibrillation in patients undergoing coronary artery bypass grafting. In-hospital mortality was higher in the Atorvastatin-group compared with the No-statingroup: 124 (8.9%) versus 301 (3.7%), respectively; p=0.027). Conclusion: Perioperative atorvastatin treatment is not found to be associated with reduced postoperative atrial fibrillation and cardiac mortality in patients undergoing isolated coronary artery bypass grafting above the age of seventy years
Keywords: preoperative statin therapy; coronary artery bypass grafting; postoperative atrial fibrillation; cardiac mortality; propensity score analysis